Extremely rapid radiation belt electron losses across the magnetopause - Hensley, Alexis N.; George, Harriet; Kalliokoski, Milla; Olifer, Leonid (Frontiers in Astronomy and Space Sciences, 2025)
IntroductionThe Earth’s radiation belt environment is highly dynamic, with different processes acting on various particle populations over a range of timescales. Constraining the timescales over which these processes act is essential to both our physical understanding of the radiation belt environment and our ability to predict and mitigate space weather effects.MethodsIn this study, we leverage the GPS constellation to evaluate a radiation belt dropout that occurred on 14 May 2019, combining observations from 18 GPS satellites during this event to evaluate the dominant loss mechanism of the dropout and to constrain the timescale of this loss. This dropout affected the entire relativistic electron population, abruptly depleting the 4 MeV population by an order of magnitude following a strong magnetopause compression.ResultsWe identify magnetopause shadowing as the dominant loss mechanism during this dropout through analysis of the electron flux data and the temporal evolution of the electron phase space density with respect to the last closed drift shell. The K=0.14REG1/2, μ=3433MeV/G electron population was eliminated within 30 min at 4.8≤L*<4.9 and eliminated in 126 min at 4.5≤L*<4.6.DiscussionDropout events are typically understood to occur on timescales of several hours to a day and sub-hour dropouts have previously only been reported by a handful of studies, so this is an exceptionally rapid elimination of the relativistic population. Our results therefore reinforce that radiation belt dropouts can occur on sub-hour timescales and highlight the value of the GPS constellation (which now contains 25 satellites distributed across magnetic local time) on studying these rapid, large-scale dynamics in the Earth’s radiation belts.